Forty years of anthropogenic nutrient pressures: agriculture and domestic nitrogen and phosphorus inventory in view of sustainable nutrient management - Malagó, Anna; Bouraoui, Fayçal (Frontiers in Sustainable Food Systems, 2023)
Nitrogen and phosphorus are key to human life and crop production. However, excessive nutrient losses from agriculture affect air, soil, and water quality, with significant negative effects on terrestrial and aquatic ecosystems. Domestic nutrient emissions, in particular untreated wastewater, also negatively affect water ecosystems. European policies had a crucial role in contrasting nutrient pollution, but the assessment of the impact of these regulations requires an understanding of nutrient inputs and losses from land to sea. In this study, we quantified nutrient inputs in a cross-continental domain (Europe–Africa–Asia) in all regions discharging into the European seas. We reconstructed the time series for the 1979–2019 periods of high spatial resolution anthropogenic nutrient pressures including nitrogen atmospheric deposition, mineral fertilizers and organic N and P fertilizers, N and P from sewer connection, and improved and unconnected systems from urban and rural populations. We investigated regional differences and how existing legislation has affected nutrient inputs.